Comparison of Macrozoobenthos Community Structure in Reclaimed and Natural Beaches in Padang City, West Sumatra - Helda, Helda; Tanjung, Afrizal; Thamrin, Thamrin (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
dang City is one of the cities with a long coastline. The Padang City government has made many reforms to manage the beach area as a tourist attraction. This research aimed to determine the comparison of macrozoobenthos community structure, including species composition, species abundance, relative abundance, diversity index, similarity index, dominance index, and distribution patterns in the reclaimed and natural beaches of Padang City, West Sumatra Province. The method used was purposive sampling with sample collection using the transect method. The results of this study indicate that the water quality in Padang City, West Sumatra, is sufficiently good to support macrozoobenthos life. The highest species abundance of macrozoobenthos was found at the Reclamation Beach Station. The macrozoobenthos species found belong to 2 classes: Gastropoda and Crustacea. The Gastropoda class consists of 4 species: Babylonia spirata, Pila ampullacea, Pila occidentalis, and Nerita fulgurans, while from the Crustacea class, three species were found: Ashtoret lunaris, Hemigrapsus takanoi, and Emerita sp. Meanwhile, the lowest abundance was found at the Natural Beach Station, where the species belonging to the Crustacea class, specifically H.takanoi, was found. The species diversity of macrozoobenthos at the Natural Beach Station is considered low but moderate at the Reclamation Beach Station. Similarity at the Natural Beach Station is low, while at the Reclamation Beach Station, it is high. Additionally, there is a dominant species at the Natural Beach Station, whereas no dominant species were found at the Reclamation Beach Station. The distribution pattern of macrozoobenthos in the coastal waters of Padang City is categorized as clustered distribution.